Activation of membrane-located Ca2+ channels by hop beta acids and their tricyclic transformation products - Schulz, Carolin; Fritz, Nikolas; Sommer, Thomas; Krofta, Karel; Friedland, Kristina; Pischetsrieder, Monika (Food Chemistry, 2018)
Beta-bitter acids of hops (lupulones) revealed sedative and antidepressant-like effects in animal studies. Transformation of beta-acids during beer brewing leads to the formation of tricyclic transformation products, which have a close structural analogy to hyperforin. The latter compound is responsible for the antidepressant activity of St. John's wort by activation of TRPC6 cation channels in neuronal-like cells leading to Ca2+ influx. In this study, nortricyclolupones, dehydrotricyclolupones, and tricyclolupones were isolated from a wort-boiling model and their structures were elucidated by UHPLC-DAD, UHPLC-ESI–MS/MS and 1D/2D-NMR spectroscopy. Beta-bitter acids and their transformation products induced Ca2+ influx in PC12 cells to the same extent as hyperforin. Application of a Ca2+-free environment abolished the Ca2+ elevation, indicating that the increase is mediated by influx across the plasma membrane. Thus, activation of neuronal-like Ca2+-channels by lupulones and tricyclolupones represent a novel mechanism contributing to the antidepressant activity of hops.
Keywords: Antidepressant; beta-bitter acids; Ca2+ influx; Hops; Lupulones; Neuronal-like cells; Tricyclolupones

Quantification of co-, n-, and ad-lupulone in hop-based dietary supplements and phytopharmaceuticals and modulation of their contents by the extraction method - Schulz, Carolin; Chiheb, Chafia; Pischetsrieder, Monika (Journal of Pharmaceutical and Biomedical Analysis, 2019)
Hop β-bitter acids (lupulones) are health-beneficial components of Humulus lupulus L. showing, for example, antidepressant-like effects in vitro. Despite of the widespread use of hops for medicinal purposes, the concentrations of lupulones in hop-based drugs have not been reported yet. The present study developed, validated, and applied a method with external calibration, which allows for the first time separate quantification of co-, n-, and ad-lupulone in hop-based drugs by UHPLC‒DAD. Concentrations between ‘not detectable’ and 2.7 mg/mL co-lupulone, 2.2 mg/mL nlupulone, or 0.7 mg/mL ad-lupulone were measured in nine different commercial dietary supplements and phytopharmaceuticals. Only one hop tincture contained sufficient lupulone to possibly exert potential antidepressant effects. Aiming for products with increased lupulone content, the extraction efficiency of different solvents was investigated. Complete extraction of lupulones from raw hops was achieved by organic solvents including methanol and ethanol, whereas aqueous mixtures resulted in low recovery. These results indicate that adapted extraction conditions may result in more effective hops product
Keywords: β-bitter acids; dietary supplements; hops; lupulones; phytopharmaceuticals; UHPLC-DAD.